Hybrid Printing Metal-mesh Transparent Conductive Films with Lower Energy Photonically Sintered Copper/tin Ink. Issue 1 (December 2017) - Chen, Xiaolian; Wu, Xinzhou; Shao, Shuangshuang; Zhuang, Jinyong; Xie, Liming; Nie, Shuhong; Su, Wenming; Chen, Zheng; Cui, Zheng
Abstract With the help of photonic sintering using intensive pulse light (IPL), copper has started to replace silver as a printable conductive material for printing electrodes in electronic circuits. However, to sinter copper ink, high energy IPL has to be used, which often causes electrode destruction, due to unreleased stress concentration and massive heat generated. In this study, a Cu/Sn hybrid ink has been developed by mixing Cu and Sn particles. The hybrid ink requires lower sintering energy than normal copper ink and has been successfully employed in a hybrid printing process to make metal-mesh transparent conductive films (TCFs). The sintering energy of Cu/Sn hybrid films with the mass ratio of 2:1 and 1:1 (Cu:Sn) were decreased by 21% compared to sintering pure Cu film, which is attributed to the lower melting point of Sn for hybrid ink. Detailed study showed that the Sn particles were effectively fused among Cu particles and formed conducting path between them. The hybrid printed Cu/Sn metal-mesh TCF with line width of 3.5 μm, high transmittance of 84% and low sheet resistance of 14 Ω/□ have been achieved with less defects and better quality than printed pure copper metal-mesh TCFs.